Ten thousand sorrows the extraordinary journey of a Korean war orphan - Kim, Elizabeth (Doubleday, 2000)
After her grandfather and uncle kill her mother for the sin of being with an American soldier, Kim is dumped in an orphanage in postwar Korea. Adopted by a pastor and his wife from the U.S., one form of abuse merely replaces another, as Kim struggles to survive to adulthood.